Hippocampal Astrogliotic Reduction in Scopolamine Hydrobromide-Induced Alzheimer’s Type Cognitive Dysfunction Wistar Rats Following Administration of Aqueous Extract of Telfairia Occidentalis (pumpkin) seeds. (Nigerian Journal of Physiological Sciences, 2021)
Astrocytes are small star-shaped glial cells that maintain normal human brain physiology including secretion of several active compounds and the formation of blood brain barrier. Reactive astrocytes support regenerating axons and also, actuate some genes responsible for the induction of synapse formation. In this study, the effect of aqueous extract of Telfairia occidentalis seeds on hippocampal astrogliosis was probed using scopolamine-induced Alzheimer’s type cognitive dysfunction Wistar rats. Thirty Wistar rats weighed between 180-200g were randomly grouped into five designated A, B, C, D and E.  Each group contained six rats. Alzheimer’s type cognitive dysfunction was induced in groups B to E by administering intraperitoneally, 1 mg/kg body weight of scopolamine for seven days before Donepezil and the aqueous extract of Telfairia occidentalis seeds for fourteen days. Twenty-four hours after the last administration, the animals were sacrificed; their brain tissues perfused and stained with glial fibrillary acidic protein (GFAP) dye. Results revealed prominently stained astrocytes with their processes intact (group A). Some densely stained numerous astrogliosis with hypertrophied fibres were noticed in group B. Group C demonstrated prominent astrocytes with hypertrophied fibres, group D, moderately stained astrogliosis with hypertrophied fibres while group E showed numerous astrocytes with prominent nuclei and hypertrophied fibres. In conclusion, there was reduced hippocampal astrogliosis mostly in group D treated with Telfairia occidentalis which may neutralize oxidative stress and enhanced learning and memory in the Wistar rats of the present study.